Ethical aspects of reporting on juvenile crime in Serbia - Kovacevic, Milica D. (Sociološki pregled, 2024)
The subject of the paper is reporting on juvenile crime in Serbia on the websites of daily newspapers Kurir and Politika By applying the content analysis, the author intended to determine whether reporting was approached professionally, as well as whether journalists dealt with the causes of juvenile delinquency, while at the same time trying to educate readers about the specific characteristics of this phenomenon. The aim of the paper is to examine the compliance of media coverage with the relevant norms that bind journalists. The results of the research indicate that, in a formal and legal sense, media reporting is in compliance with the positive regulations governing this area, but that the ethics could be at a higher level. Although reporting is generally based on the named sources and does not contradict the principle of privacy protection, there is no indication of the broader context in which juvenile delinquency manifests itself. The media image of juvenile crime created by the analyzed websites emphasizes violent crime, although juveniles in Serbia predominantly commit property crimes. The author concludes that there is a need for more substantive reporting that would not be limited to the mere transmission of information about the most serious forms of juvenile crime, but would also educate the general public about this topic.
Keywords: media; juvenile crime; professional reporting